Psychosocial burden and professional and social support in patients with hereditary transthyretin amyloidosis (ATTRv) and their relatives in Italy - Lorenza Magliano (Orphanet Journal of Rare Diseases, 2021)
Abstract Background Hereditary transthyretin amyloidosis (hATTR), alias ATTR variant (ATTRv) is a severe and disabling disease causing sensory and motor neuropathy, autonomic dysfunction, and cardiomyopathy. The progressive decline of patient’s functional autonomy negatively affects the patient’s quality of life and requires increasing involvement of relatives in the patient’s daily life. Family caregiving may become particularly demanding when the patient is no longer able to move independently. This study is focused on the psychosocial aspects of ATTRv from the patient and relative perspectives. In particular, it explored: the practical and psychological burdens experienced by symptomatic patients with ATTRv and their key relatives and the professional and social network support they may rely on; whether burden varied in relation to patients’ and relatives’ socio-demographic variables, patients’ clinical variables, and perceived professional and social network support; and, any difference in burden and support between patients and their matched relatives. Methods The study was carried out on symptomatic patients included in the ATTRv Italian national registry and living with at least one adult relative not suffering from severe illness and being free from ATTRv symptoms. Patients and relatives’ assessments were performed using validated self-reported tools. Results Overall, 141 patients and 69 relatives were evaluated. Constraints of leisure activities, feelings of loss and worries for the future were the consequences of ATTRv most frequently reported by patients and relatives. Both in patients and their relatives, the burden increased with the duration of symptoms and the level of help in daily activities needed by the patient. In the 69 matched patient-relative pairs, the practical burden was significantly higher among the patients than among their relatives, while the psychological burden was similar in the two groups. Moreover, compared to their relatives, patients with ATTRv reported higher levels of professional and social network support. Conclusions These results show that ATTRv is a disease affecting quality of life of both patients and their families. Supporting interventions should be guaranteed to patients, to facilitate their adaptation to the disease, and to their families, to cope as best as possible with the difficulties that this pathology may involve.